2016
DOI: 10.3109/24699322.2016.1167245
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a fibula graft cutting guide for mandibular reconstruction: experiment with rapid prototyping mandible model

Abstract: Objective: We examined whether cutting a fibula graft with a surgical guide template, prepared with computer-aided design/computer-aided manufacturing (CAD/CAM), would improve the precision and accuracy of mandibular reconstruction. Methods: Thirty mandibular rapid prototype (RP) models were allocated to experimental (N ¼ 15) and control (N ¼ 15) groups. Thirty identical fibular RP models were assigned randomly, 15 to each group. For reference, we prepared a reconstructed mandibular RP model with a three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…The results achieved with the MUC-Jig occasionally differed from those achieved with the template at >30 • angles. However, this deviation is still within limits, and it hardly differs from length [16][17][18][22][23][24][25] and angle [18,26,27] deviations of other studies. In the present study, the largest length deviations were usually located in the regions furthest away from the stop.…”
Section: Discussioncontrasting
confidence: 67%
“…The results achieved with the MUC-Jig occasionally differed from those achieved with the template at >30 • angles. However, this deviation is still within limits, and it hardly differs from length [16][17][18][22][23][24][25] and angle [18,26,27] deviations of other studies. In the present study, the largest length deviations were usually located in the regions furthest away from the stop.…”
Section: Discussioncontrasting
confidence: 67%
“…[ 54 ] Validation Study Japan Cranial Surgery Craniotomy Training, Simulation 2016 Lim SH et Al. [ 55 ] Validation Study Korea Macillo-Facial Surgery Mandible reconstruction Planning 2015 Pacione D et al [ 56 ] Pilot Study USA Maxillofacial Surgery Deformity of the skull base and craniovertebral junction Planning 2015 Chan HHL et al [ 57 ] Case Series Canada Maxillofacial Surgery Head and neck surgery Training, Simulation 2015 Dickinson KJ et al [ 58 ] Case Report USA Maxillofacial Surgery Endoscopic resection in esophagus Planning 2015 Hochman JB et al [ 59 ] Comparative Study Canada Maxillofacial Surgery Mastoidectomy and skull base surgery Training 2015 Cohen J et al [ 60 ] Validation Study USA Maxillofacial Surgery Mastoidectomy Training 2015 Lim C et al [ 17 ] Case Series Australia - New Zealand Maxillofacial Surgery Orbital reconstruction Planning 2015 Rose AS et al [ 61 ] Case Report USA ENT Surgery Mastoidectomy Planning, Simulation 2015 Ernoult C. et Al. [ 62 ] Case Series France Maxillofacial Surgery ...…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, computer‐assisted surgery (CAS) has been recognized as a valuable method to support FFF mandibular reconstruction . Nowadays, the most popular CAS technique is computer‐aided design and manufacturing (CAD/CAM).…”
Section: Introductionmentioning
confidence: 99%
“…In this method, a virtual surgery plan (VSP) is developed, and then patient‐specific osteotomy guides are manufactured according to the VSP. Using the guides, the surgeon can harvest the FFF with predefined shape and dimensions . Whereas some studies demonstrated that use of the guides contributed to greater accuracy of the reconstruction procedures and shorter operating time, the influence of this technique on the overall treatment cost is still a matter of debate …”
Section: Introductionmentioning
confidence: 99%